Analisis dampak model kepemimpinan terhadap kinerja karyawan dan kualitas layanan pelanggan - Sadewo, Mohammad Tio Pangku (Maliki Interdisciplinary Journal, 2024)
This research aims to analyze the impact of leadership models on employee performance and customer service quality. The research method was direct observation and interviews at the Outlet and OP Service Section of PT POS Indonesia KCU Malang. The findings of this research show that the leadership style used motivates employees to enjoy the work they do more, obey existing regulations more, pressure them to work according to the salary they get and there is a process of increasing an employee’s abilities.